MANIFESTASI PROGRAM KESEJAHTERAAN SOSIAL ANAK (PKSA) DALAM MENINGKATKAN KESEJAHTERAAN SOSIAL ANAK JALANAN DI RUMAH SINGGAH ANAK MANDIRI (RSAM) YOGYAKARTA - Aulia Widya Sakina; Yuli Setyowati; Oktarina Albizzia; Anastasia Adiwirahayu (Jurnal Academia Praja, 2020)
The phenomenon of street children is one of the crucial problems that accompany the development process. The dynamics of the life of street children which are identical with the culture of poverty, are considered to deviate from the social function of children due to various activities carried out on the streets. Over the past 9 years, the Ministry of Social Affairs has implemented policies, strategies and Program Kesejahteraan Sosial Anak (PKSA) which aims to empower and meet the needs of children living on the streets, however these efforts are seen as not yet running optimally. Echoes of "Social Movements Towards a Street-Free Indonesia" as part of PKSA are still "foreign" to be heard, although statistics show a decrease in the number of street children in reality there are still many street children who carry out various activities in the corners of the city such as in traffic lights, stations , terminals and around shopping centers. This proves that protection programs and services for street children have not run effectively and are not well integrated. This study aims to determine the extent of PKSA manifestations in realizing the social welfare of street children at Rumah Singgah Anak Mandiri (RSAM) Yogyakarta. The method used in this study is a qualitative research method using descriptive analysis. After the data is collected, the data analysis technique is carried out with the stages of data selection, data presentation and drawing conclusions. So that research results can be trusted, triangulation is carried out to test the validity of research data. Based on the results of the study it can be concluded that the implementation of PKSA in Yogyakarta RSAM has a positive impact on street children. This can be seen from the achievement of the basic needs of street children who are fostered, the achievement of basic education of street children because most street children can go back to school, and the reduced time children are on the streets. Keywords: PKSA, Social Welfare, Street Children, RSAM.